Expressed sequence tags related to nitrogen metabolism in maize inoculated with Azospirillum brasilense - Pereira-Defilippi, L. [UNESP]; Pereira, E. M. [UNESP]; Silva, F. M. [UNESP]; Moro, G. V. [UNESP] (Funpec-editora, 2017)
The relative quantitative real-time expression of two expressed sequence tags (ESTs) codifying for key enzymes in nitrogen metabolism in maize, nitrate reductase (ZmNR), and glutamine synthetase (ZmGln1-3) was performed for genotypes inoculated with Azospirillum brasilense. Two commercial single-cross hybrids (AG7098 and 2B707) and two experimental synthetic varieties (V2 and V4) were raised under controlled greenhouse conditions, in six treatment groups corresponding to different forms of inoculation and different levels of nitrogen application by top-dressing. The genotypes presented distinct responses to inoculation with A. brasilense. Increases in the expression of ZmNR were observed for the hybrids, while V4 only displayed a greater level of expression when the plants received nitrogenous fertilization by top-dressing and there was no inoculation. The expression of the ZmGln1-3EST was induced by A. brasilense in the hybrids and the variety V4. In contrast, the variety V2 did not respond to inoculation.
Keywords: Zea mays L.; Nitrate reductase; Glutamine synthetase; qPCR